The thrombin generation assay distinguishes inhibitor from non‐inhibitor patients with severe haemophilia A. (11th May 2016) - Mancuso, M. E.; Chantarangkul, V.; Clerici, M.; Fasulo, M. R.; Padovan, L.; Scalambrino, E.; Peyvandi, F.; Tripodi, A.; Santagostino, E.
Abstract : Introduction: Patients with haemophilia A (HA) have impaired thrombin generation (TG) capacity and TG assay (TGA) values are linearly related to plasma factor VIII (FVIII) levels. Aim: This study carried out in patients with unmeasurable FVIII (<1 IU dL −1 ) was aimed at unravelling any difference in TG capacity in patients with or without inhibitors. Methods: Blood samples were collected from patients in a non‐bleeding state, after a 5‐day wash‐out period from last treatment. Results: TGA was performed in 102 patients with severe HA (15% with high‐responding inhibitors; 51% with null F8 mutations, that as expected were more prevalent in inhibitor than in non‐inhibitor patients). TG capacity was significantly lower in inhibitor than non‐inhibitor patients and in those with null mutations than in those with non‐null mutations. When the TG capacity was evaluated only in patients with null mutations with and without inhibitors it was lower in the presence of inhibitors. Conclusions: This study shows a greater TG impairment in inhibitor patients irrespective of FVIII levels, inhibitor titre and F8 mutation type, suggesting a role for the TGA in unravelling functional interferences of anti‐FVIII inhibitors on coagulation system activation.